Local delivery of USC-derived exosomes harboring ANGPTL3 enhances spinal cord functional recovery after injury by promoting angiogenesis - Cao, Yong; Xu, Yan; Chen, Chunyuan; Xie, Hui; Lu, Hongbin; Hu, Jianzhong (Stem cell research & therapy, 2021)
Spinal cord injury is a devastating clinical condition for which there are currently no effective therapeutic options. In the present study, we aim to investigate if the effect of an administered injection of exosomes derived from human urine stem cell (USC-Exo) embedded in hydrogel could improve the spinal cord functional recovery after injury and the underlying mechanism. Exosomes were isolated from USC and identified by transmission electron microscopy (TEM) and Western blot. Functional assays in vitro were performed to assess the effects of USC-Exo on tube formation and migration, as well as their regulatory role in the PI3K/AKT signaling pathway activation. A locally administered injection of exosome embedded in hydrogel was used for SCI treatment. The effects of USC-Exo on functional recovery and the role of the candidate protein ANGPTL3 harboring in USC-Exo for promoting angiogenesis in SCI model were assessed. In the current study, we demonstrate that a locally administered injection of USC-Exo embedded in hydrogel can pass the spinal cord blood-brain barrier and deliver ANGPTL3 to the injured spinal cord region. In addition, the administration of human USC-Exo could enhance spinal cord neurological functional recovery by promoting angiogenesis. The results of mechanistic studies revealed that ANGPTL3 is enriched in USC-Exo and is required for their ability to promote angiogenesis. Functional studies further confirmed that the effects of USC-Exo on angiogenesis are mediated by the PI3K/AKT signaling pathway. Collectively, our results indicate that USC-Exo serve as a crucial regulator of angiogenesis by delivering ANGPTL3 and may represent a promising novel therapeutic agent for SCI repair.